A SYSTEMATIC LITERATURE REVIEW ON RISK MANAGEMENT FOR INFORMATION TECHNOLOGY - Dr Anil Kumar Mahra (International Journal of Advanced Science and Technology, 2019)
In today’s information technology era, several organizations use automated digital technology and information technology application to develop their business for better maintenance of their operations. The information technology risk management plays a critical role in defending an organization’s valuable data and information assets. The main aim of information technology risk management is to protect the digital system from IT-related risk. An effective and efficient risk management process is a significant part of an efficacious information technology security program. A good IT risk management approachaim should be to protect the organization and its resources to perform their operation, not just its digital assets. Consequently, the risk management process should not be treated primarily as a technical function carried out by the IT experts who operate and manage the IT system, but as an essential management function of the organization. The purpose of this paper is to explore the field of risk management for information technology. The risks of information assets have complex nature; the management of risk of information security is addressed by different approaches. The paper provides a systematic literature review on risk management for information technology. To accomplish this purpose we conducted a Systematic Review of the literature in the popularliterature databases. It determined that there are several studies about the methods, exist different approaches about the risk analysis.